2021
DOI: 10.12911/22998993/140265
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Effect of Tourism Activities on Litter Pollution: A Case Study on Padar Island, Komodo National Park, Indonesia

Abstract: Tourism is a significant socioeconomic activity in a coastal country such as Indonesia. However, it degrades the ecosystem quality when the increasing litter pollution is poorly managed in the marine tourism area. The purpose of this research was to assess the impact of tourism on the litter pollution on the Padar Island, Komodo National Park, Indonesia, specifically on the hiking track. According to the performed investigation, plastic litter was discovered dominant on the Padar Island (131 of 146 items). It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(58 reference statements)
0
7
0
1
Order By: Relevance
“…These plastics, which are often single use, are brittle and have a low fracture resistance ( Jin et al, 2019 ). After being abandoned and exposed to the environment, these forms of plastic are at a higher hazard of rapidly deteriorating into little particles of plastic waste ( Cordova et al, 2021b , 2020; Falahudin et al, 2020 ). Moreover, the fraction of large-sized microplastics with a size of 500-1000 μm and > 1000 μm was considerable (79.69 %).…”
Section: Discussionmentioning
confidence: 99%
“…These plastics, which are often single use, are brittle and have a low fracture resistance ( Jin et al, 2019 ). After being abandoned and exposed to the environment, these forms of plastic are at a higher hazard of rapidly deteriorating into little particles of plastic waste ( Cordova et al, 2021b , 2020; Falahudin et al, 2020 ). Moreover, the fraction of large-sized microplastics with a size of 500-1000 μm and > 1000 μm was considerable (79.69 %).…”
Section: Discussionmentioning
confidence: 99%
“…The predominant litter found here directly results from specific human activities, as highlighted in this research. The significant presence of cigarette butts, candy wrappers, wet tissues/wipes, and outsoles from shoes/sandals indicates primary activities leading to pollution, such as smoking, food and beverage consumption, and hiking (Cordova et al, 2021). This specific nature of litter can be attributed to the recreational activities promoted by the park (Cordova et al, 2021).…”
Section: Environmental Impacts Of the Tourism Activitiesmentioning
confidence: 99%
“…The significant presence of cigarette butts, candy wrappers, wet tissues/wipes, and outsoles from shoes/sandals indicates primary activities leading to pollution, such as smoking, food and beverage consumption, and hiking (Cordova et al, 2021). This specific nature of litter can be attributed to the recreational activities promoted by the park (Cordova et al, 2021). The park's vast natural landscape, hiking trails, and scenic viewpoints attract numerous tourists.…”
Section: Environmental Impacts Of the Tourism Activitiesmentioning
confidence: 99%
“…Sutawa (2012) and Lanya et al, (2017) reported that the land use in agriculture has remarkably transformed to tourism facilities as the development in the tourism sector took place. In the same vein, Cordova et al (2021) identified the waste problem as an emerging challenge that happened in Komodo Island as a tourism place.…”
Section: Introductionmentioning
confidence: 98%